Accurate Simulation of MPPT Methods Performance When Applied to Commercial Photovoltaic Panels. (22nd March 2015) - Cubas, Javier; Pindado, Santiago; Sanz-Andrés, Ángel
Abstract : A new, simple, and quick-calculation methodology to obtain a solar panel model, based on the manufacturers' datasheet, to perform MPPT simulations, is described. The method takes into account variations on the ambient conditions (sun irradiation and solar cells temperature) and allows fast MPPT methods comparison or their performance prediction when applied to a particular solar panel. The feasibility of the described methodology is checked with four different MPPT methods applied to a commercial solar panel, within a day, and under realistic ambient conditions.